2012
DOI: 10.2136/sssaj2011.0354
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Nondestructive Total Elemental Analysis of Vertisol Soils using Portable X-ray Fluorescence

Abstract: Portable X-ray fluorescence (PXRF) spectrometry can provide rapid and nondestructive analyses of agriculturally important elements in soil. To assess the applicability of PXRF for total element analysis of Vertisols, 20 soils were collected across northern New South Wales (NSW), Australia. Comparison of PXRF results were made with conventional standard microwave aqua regia (AR) digestion followed by inductively couple plasma optical emission spectroscopy (ICP-OES) analysis, laboratory X-ray fluorescence (LXRF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…But recent studies have also shown that PXRF can be employed to calibrate for a range of soil properties (McLaren et al, 2012;Weindorf et al, 2009Weindorf et al, , 2012bWeindorf et al, , 2012cWeindorf et al, , 2013aZhu and Weindorf, 2009;Zhu et al, 2011) and in addition can also be used to investigate the degree of soil weathering (Che et al, 2012). In a recent study, for example, Wang et al (2013) also presented the complementary use of PXRF and Fourier transform NIR spectroscopy to predict soil texture.…”
Section: Pxrf For Measuring Soil Contaminantsmentioning
confidence: 99%
“…But recent studies have also shown that PXRF can be employed to calibrate for a range of soil properties (McLaren et al, 2012;Weindorf et al, 2009Weindorf et al, , 2012bWeindorf et al, , 2012cWeindorf et al, , 2013aZhu and Weindorf, 2009;Zhu et al, 2011) and in addition can also be used to investigate the degree of soil weathering (Che et al, 2012). In a recent study, for example, Wang et al (2013) also presented the complementary use of PXRF and Fourier transform NIR spectroscopy to predict soil texture.…”
Section: Pxrf For Measuring Soil Contaminantsmentioning
confidence: 99%
“…The use of field-portable XRF devices offer an exiting, albeit expensive, approach to rapidly identifying and quantifying local variation in lithology (Zhu et al, 2011;Weindorf et al, 2012;McLaren et al, 2012). In arid environments, multispectral (Landsat TM), and hyperspectral (AVIRIS) remote sensing has been used to delineate variation in surface mineralogy and sediment source (Scull et al, 2003;Levi and Rasmussen, 2014).…”
Section: Options For Detailed Mapping Of Lithologic Variabilitymentioning
confidence: 99%
“…Precision agriculture presents potential to increase crop yield. Hence, efforts have been made towards the development of faster, precise, and accurate methods that allow accessing the plant and soil nutritional status in field. This analytical strategy will permit the readily correction of nutritional deficiency.…”
Section: Introductionmentioning
confidence: 99%